The concept of Czech pronunciation exercise books for foreigners from the ProCzeFor (Pronunciation of Czech for Foreigners) project - Veronkova, Jitka; Palkova, Zdena (Bohemica Olomucensia, 2023)
Two printed exercise books for practicing Czech pronunciation for foreigners contain speech material reflecting the sound characteristics of Czech and the most difficult sound phenomena for non-native speakers. All the exercises are connected to the online app with audio tracks and other functions.
Keywords: Czech as L2; Czech for foreigners; pronunciation; perception; articulation; sound